Recommendation practice on childhood vaccine and its determinants among pediatricians in China - Shu-jie ZANG; Si-meng HU; Qian WANG (Editorial Office of Chinese Journal of Public Health, 2022)
Objective To examine the behavior of recommendation on childhood vaccines and its influencing factors among pediatricians. Methods Using convenient sampling, we conducted a web-based voluntary anonymous questionnaire survey among 289 pediatricians at seven professional training sites in Beijing-Tianjin-Hebei Region and six municipalities in central, southern and northern China during November - December 2020. Multivariate ordinal logistic regression analysis was adopted to explore factors associated with the recommendation behavior. ResultsOf all the respondents, 25.3% (73/289), 50.2% (145/289), and 24.5% (71/289) reported often, sometimes, and occasionally recommending childhood vaccines to the parents of child clinic attendees, respectively. The main reason reported by 89.7% of the pediatricians not recommending childhood vaccines was there being no requirements and responsibilities on the vaccination recommendation. Among all the respondents, only 30.1% (87/289) considered being with adequate knowledge about childhood vaccines to answer relevant questions from child clinic attendees' parents, although 84.8% (245/289) reported having been consulted by the parents on the issues during past one year. The results of multivariate logistic regression analysis revealed that the respondents with following characteristics were more likely to conduct the vaccination recommendation: with senior professional titles (odds ratio [OR] = 2.124, 95% confidence interval [95% CI]: 1.169 - 3.858), having received influenza vaccination (OR = 2.237, 95% CI: 1.296 - 3.861), ever receiving vaccine-related training (OR = 1.830, 95% CI: 1.112 - 3.012), having been consulted by child clinic attendees' parents frequently (OR = 6.604, 95% CI: 3.042 - 14.338), with adequate knowledge about childhood vaccines (OR = 1.984, 95% CI: 1.152 - 3.418), and having perceived professional responsibilities for the vaccination recommendation (OR = 5.6, 95% CI: 3.083 - 10.172). Conclusion Recommendation on childhood vaccines is not often conducted by pediatricians and the situation needs to be improved in China.